Improving Teacher Professionalism Through Empowering CS50X Harvard University Alumni in Developing Technology Based Teaching Materials - Roslina; Nisa , Miftachurohmah; Nasruddin, Nasruddin; Nursamsir, Nursamsir; Rosyana , Marlianti; Nurhaeliani, Nurhaeliani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Teacher professionalism at SMA Negeri 1 Lasolo remains low, as evidenced by the underutilization of the school's website despite its availability since 2019. Meanwhile, one of the teachers at the school is a CS50X Harvard University alumnus, presenting an opportunity to enhance the professionalism of other teachers. Therefore, this study aims to empower the CS50X alumnus to improve teacher professionalism through the development of technology-based teaching materials. This study employs a research and development (R&D) approach using the MPI + R method, involving 29 teachers as participants. The MPI + R method consists of Material, Practice, Innovation, and Reflection phases, designed to enhance teacher competency through peer teaching. Data were collected using questionnaires, observations, and document analysis, then analyzed using paired t-tests and correlation analysis to measure the effectiveness of the program. The findings indicate that the program successfully enhanced teachers' skills in developing application-based teaching materials integrated with the school's digital platform. In kind off Google Sites. Furthermore, teachers showed a significant increase in motivation and interest in utilizing technology for instructional purposes. However, challenges such as infrastructure limitations and internet connectivity issues were identified as barriers to technology adoption. This study concludes that empowering CS50X Harvard University alumni through peer teaching is an effective strategy for improving teacher digital competencies. It is recommended that schools and policymakers invest in infrastructure improvements and provide ongoing teacher training to maximize technology integration in education. Moreover, this program contributes to strengthening the Merdeka Curriculum by enhancing teachers’ digital readiness in classroom instruction.